2012
DOI: 10.1590/s1517-83822012000300042
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of essential oils against Lactobacillus rhamnosus and starter culture in fermented milk during its shelf-life period

Abstract: The use of essential oils in foods has attracted great interest, due to their antagonistic action against pathogenic microorganisms. However, this action is undesirable for probiotic foods, as products containing Lactobacillus rhamnosus. The aim of the present study was to measure the sensitivity profile of L. rhamnosus and a yogurt starter culture in fermented milk, upon addition of increasing concentrations of cinnamon, clove and mint essential oils. Essential oils were prepared by steam distillation, and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
2
13
1
Order By: Relevance
“…Marafon et al () found the number of viable probiotics to be higher when spices cardamom and cinnamon were used, but not with nutmeg. Moritz, Rall, Saeki, and Júnior () reported the count of isolated L. rhamnosus treated with cinnamon EO to be reduced by 1 log, and cell counts were above the minimum count of 10 6 cfu/mL. Previously, De Lacey, Pérez‐Santín, López‐Caballero, and Montero () found green tea extracts to affect positively the survival of L. paracasei LAFTI‐L26, L. acidophilus LAFTI‐L10 and B. animalis ssp.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Marafon et al () found the number of viable probiotics to be higher when spices cardamom and cinnamon were used, but not with nutmeg. Moritz, Rall, Saeki, and Júnior () reported the count of isolated L. rhamnosus treated with cinnamon EO to be reduced by 1 log, and cell counts were above the minimum count of 10 6 cfu/mL. Previously, De Lacey, Pérez‐Santín, López‐Caballero, and Montero () found green tea extracts to affect positively the survival of L. paracasei LAFTI‐L26, L. acidophilus LAFTI‐L10 and B. animalis ssp.…”
Section: Resultsmentioning
confidence: 97%
“…C1 containing probiotic culture and C samples were preferred more than the others in the present study. Moritz et al (2012) found in their study no statistical difference between the concentrations from 5% (lowest concentration) to 0.04% cinnamon EO and a mean acceptability score to be 6.28 for 0.04% cinnamon EO. Jimborean et al (2016) reported orange EOs fortified yogurt to get high acceptability score (7.50).…”
Section: Physical and Chemical Characteristics Of Yogurt Samplesmentioning
confidence: 83%
See 1 more Smart Citation
“…PO is one of the naturally-flavored oils and obtained usually from roasted seeds to give good characteristic flavor. Yang et al (2012) reported the consumer acceptability of perilla oil porridges, Moritz et al (2012) have demonstrated that the consumer acceptability of essential oils used in fermented milk. In this research, nisin and PO synergistically and significantly inhibited the growth of S. aureus and L. monoctogenes in milk samples.…”
Section: Discussionmentioning
confidence: 99%
“…Only a sublethal effect of clove essential oil was observed against probiotic bacterial species L. rhamnosus, indicating the resistance of these microorganisms to clove essential oil. [50] This hints towards the possibility of harnessing their and E.coli, the optimum conditions for best activities of both-clove essential oil and lactobacilli, are a few criteria required to be considered to gain an overall increase in their combined anti-microbial actions.…”
Section: Probiotics (Lactobacilli) Against Pathogenic Ecolimentioning
confidence: 99%